Spatial agglomeration and productivity of textile and leather manufacturing in the Punjab province of Pakistan - Asim Iqbal; Muhammad Wasif Siddiqi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
This study investigates whether spatial agglomeration of textile and leather industry facilitates to enhance its own productivity at establishment level in the Punjab province of Pakistan. The empirical analysis is based on the survey data for the years 1995-96, 2000-2001 and 2005-06 collected from the Punjab Bureau of Statistics (PBS). The production function framework has been utilized. The results of production function suggest that spatial agglomeration of textile and leather industry plays a vital role in determining the productivity of establishments. The impact of localization (specialization) is positive and stronger than urbanization (diversification) which implies that locating manufacturing establishments in a particular district leads to enhance the productivity of establishments. Therefore, government policy should be biased to promote localization of textile and leather industry.
Keywords: 330; Managerial entrenchment; cost of capital stock; systematic risk; sales growth; leather; textile